An investigation of sugar-sweetened beverage consumption among Canadian youth - Davis, Laura (2016)
Thesis (Master, Community Health & Epidemiology) -- Queen's University, 2016-08-08 16:01:46.322 Background: Consumption of sugar-sweetened beverages (SSBs) is an important public health problem in Canada, especially among adolescents. Estimates show that rates of SSB consumption are particularly high in the northern territories, especially in Nunavut. This is concerning given that regular SSB consumption is associated with obesity, diabetes and tooth decay, among other health concerns. Objectives: This thesis has two objectives. The first is to describe SSB consumption patterns among adolescents from Nunavut specifically, all three territories combined and the provinces.The second is to determine the association between individual and cumulative school food programs and SSB consumption. Methods: Data were obtained from the Health Behaviour in School-aged Children study (HBSC); a cross-sectional survey of Canadian youth in grades 6-10. All frequencies for food and beverage consumption were obtained from a 7-day food frequency questionnaire. SSB consumption consisted of a composite measure including soft drinks, sports drinks and energy drinks. The types of school food programs were obtained from an administrative questionnaire filled out by each school’s Principal or delegate. Multilevel multivariate Poisson regression models were used to examine the associations between school food programs and SSB consumption. Results: Youth from Nunavut consumed the most SSBs (53.1% in 2010 and 55.0% in 2014 were daily consumers), followed by youth from the territories (31.1% in 2010 and 27.0% in 2014), then youth from the provinces (24.3% in 2010 and 19.1% in 2014). No significant relationships were found between school food programs and daily SSB consumption. Two school food programs were weakly associated with weekly SSB consumption: nutrition month activities (RR=0.93,CI=0.89, 0.98) and healthy options in the snack bar (RR=1.07, CI=1.01, 1.14). Conclusions:Rates of SSB consumption were highest among Nunavummiut youth ...